2016
DOI: 10.1007/s10519-016-9779-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Maternal Smoking during Pregnancy on Offspring Externalizing Problems: Contextual Effects in a Sample of Female Twins

Abstract: Studies of maternal smoking during pregnancy (MSDP) suggest increased risk for cognitive impairment and psychiatric outcomes. However, it is uncertain whether these associations are the direct result of MSDP or related to confounding familial variables associated with MSDP. The current study employed propensity score analysis to examine the effects of MSDP on offspring EXT using data from a large sample of 979 unrelated mothers. Logistic regression models were used to determine the propensity that the offsprin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 56 publications
1
26
0
Order By: Relevance
“…The two final SDP papers used a propensity scoring approach in the Missouri Adolescent Female Twin Study. Palmer et al (2016) examined how the effects of maternal SDP on offspring externalizing behavior may differ if the mother smoked only during her first trimester as compared to smoking throughout her pregnancy. The findings indicated that there was a direct effect of maternal SDP on offspring externalizing behavior, but that this direct association varied in a way consistent with a dose–response effect and was confounded, in part, with familial factors.…”
Section: Contents Of the Special Issuementioning
confidence: 99%
“…The two final SDP papers used a propensity scoring approach in the Missouri Adolescent Female Twin Study. Palmer et al (2016) examined how the effects of maternal SDP on offspring externalizing behavior may differ if the mother smoked only during her first trimester as compared to smoking throughout her pregnancy. The findings indicated that there was a direct effect of maternal SDP on offspring externalizing behavior, but that this direct association varied in a way consistent with a dose–response effect and was confounded, in part, with familial factors.…”
Section: Contents Of the Special Issuementioning
confidence: 99%
“…In addition to this potential teratogenic effect, associated familial and contextual factors may also play a role in the development of problem behavior (Ellingson, Goodnight, Van Hulle, Waldman, & D’Onofrio, 2014; Knopik, 2009; Massey & Compton, 2013; Palmer, Bidwell, Heath, Brick, Madden, & Knopik, 2016). For instance, mothers who smoke during pregnancy are often younger, single parents (Ellingson, Rickert, Lichtenstein, Langstrom, & D’Onofrio, 2012) who are of lower income with less education (Cornelius, Leech, & Goldschmidt, 2004).…”
Section: Maternal Smoking Psychopathology and Parentingmentioning
confidence: 99%
“…There is debate about the robustness of the association between MSDP and psychological and psychopathological functioning in offspring (D'Onofrio et al, ; Gaysina et al, ; Palmer et al, ). Most well‐powered studies have found psychological differences in offspring by whether their mother smoked during pregnancy (e.g., greater externalizing symptomatology; D'Onofrio et al, ; Gaysina et al, ; Kovess et al, ; Palmer et al, ). These studies, however, have also shown that unobserved factors account for this association.…”
Section: Discussionmentioning
confidence: 99%